UPAYA MENINGKATKAN LOYALITAS PELANGGAN SKINCARE MS GLOW MELALUI STRATEGI CUSTOMER BONDING - Sutanty, Marisa; Rahayu, Sri; Kayanti, Ade (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the effect of customer bonding strategies on customer loyalty using Ms Glow skincare. The type of this study was causal associative study. The type of data used in this study was quantitative data obtained directly from respondents using a questionnaire. The respondents in this study were 50 Ms Glow skincare customers in Sumbawa District who were determined using accidental sampling techniques. Data processing was carried out using SPSS software. Data analysis was carried out using simple linear regression analysis techniques, partial hypothesis testing (t test), and coefficient of determination test (R2). The results of this study showed that the customer bonding strategy had a positive and significant effect on customer loyalty using Ms Glow skincare in Sumbawa District. The contribution of customer bonding strategies in influencing customer loyalty using Ms Glow skincare in Sumbawa District was 39.1%, while the remaining of 60.9% was influenced by other variables not examined in this study model, such as perceived value, quality of product, quality of service, prices, promotions and customer satisfaction.